Genetic variation in CYP2D6 impacts neural activation during cognitive tasks in humans - Stingl, Julia; Esslinger, Christine; Tost, Heike; Bilek, Edda; Kirsch, Peter; Rietschel, Marcella; Meyer-Lindenberg, Andreas (NeuroImage, 2011)
The drug metabolizing cytochrome P450 2D6 enzyme (CYP2D6) is highly expressed in brain and potentially involved in neurotransmitter biotransformation. Here, we report the effect of the CYP2D6 genotype on brain activation during a working memory and an emotional face matching task measured with fMRI. Subjects were taken from an ongoing large scale multicenter imaging genetic study. CYP2D6 genotyping of the alleles *2, *3, *4, *5, *6, *9, *10, *17, *35, *41 and the duplication was performed in N=114 healthy drug free individuals. All individuals had completed two tasks in functional brain imaging: an n-back working memory task and an implicit emotional face matching task. Contrast images were analyzed in second-level random effects models with CYP2D6 enzyme activity levels as regressor of interest and age, sex and scanning site as covariates. In the working memory task, a significant effect of CYP2D6 genotype was found in the fusiform gyrus and the precuneus. In the emotional face matching task, an effect was detected in the cuneus. No significant activation results were found in the thalamus. A conjunction analysis confirmed a significant joint effect of the CYP2D6 association in both regions. In both tasks activation increased with increasing CYP2D6 activity. In conclusion, we confirmed a central nervous system effect of CYP2D6 activity in a large independent sample using a different imaging modality, and provide evidence that basic cognitive processes related to such as alertness may be impacted.
Gesehen am 19.04.2018